2015
DOI: 10.1097/mco.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

You are what you eat

Abstract: Purpose of review The O-linked N-acetylglucosamine (O-GlcNAc) modification is both responsive to nutrient availability and capable of altering intracellular cellular signaling. We summarize data defining a role for O-GlcNAcylation in metabolic homeostasis and epigenetic regulation of development in the intrauterine environment. Recent Findings O-GlcNAc Transferase (OGT) catalyzes nutrient-driven O-GlcNAc addition and is subject to random X-inactivation. OGT plays key roles in growth factor signaling, stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Moreover, a deregulation in the O -GlcNAcylation cycling is involved in the etiology of diverse pathologies, such as type-2 diabetes, Alzheimer’s, and cancers ( 6 ). Intriguingly, due to the correlation between UDP-GlcNAc, O -GlcNAcylation, and nutrients availability, diseases associated with unhealthy diet and metabolic disorders may be tightly linked to O -GlcNAcylation imbalance ( 28 ). It is, therefore, crucial to better understand through which metabolic mechanisms lifestyles negatively impact human health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a deregulation in the O -GlcNAcylation cycling is involved in the etiology of diverse pathologies, such as type-2 diabetes, Alzheimer’s, and cancers ( 6 ). Intriguingly, due to the correlation between UDP-GlcNAc, O -GlcNAcylation, and nutrients availability, diseases associated with unhealthy diet and metabolic disorders may be tightly linked to O -GlcNAcylation imbalance ( 28 ). It is, therefore, crucial to better understand through which metabolic mechanisms lifestyles negatively impact human health.…”
Section: Discussionmentioning
confidence: 99%
“…For changes in protein methylation, part of the mechanism of action is through the post-translational nitrosyliron complex formation in the catalytic pocket of the demethylase lysine demethylase 3A (KDM3A) [59]. Another important post-translational modification integrating metabolic redox signaling to epigenetic pathways is protein O-GlcNAcylation that will be discussed in the next section [60-62]. …”
Section: Epigenetics and Redox Dependent Metabolic Regulationmentioning
confidence: 99%
“…In this respect the post-translational modification of proteins by the attachment of β-N-acetylglucosamine on serine and threonine residues via an O-linkage (O-GlcNAc) is achieving particular prominence because of its intimate relationship with glycolysis, response to oxidative stress and as a nexus linking nutrient signaling to gene expression [60-62, 69, 70]. In contrast to typical glycosylation, O-GlcNAcylation is a dynamic and reversible modification, regulated by O-GlcNAc transferase (OGT), a glycosyl transferase that uses UDP-GlcNAc to catalyze the attachment of O-GlcNAc to proteins and O-GlcNAcase, a hexosaminidase, which catalyzes its removal.…”
Section: The Glcnac Pathway and Mitochondrial Function Under Stressmentioning
confidence: 99%
“…OGT and OGA interact with the GATA-1-FOG-1-Mi2␤ (NuRD) repressor complex at the A ␥-globin promoter, and O-GlcNAcylation of the NuRD chromatin-remodeling complex is necessary for GATA-1-FOG-1-Mi2␤ repressor formation (20). Other studies have demonstrated that O-GlcNAc cycling on chromatin modifiers is critical for modulation of gene transcription and normal development (33,34). Thus, O-GlcNAc might regulate hematopoietic cell differentiation and maturation.…”
mentioning
confidence: 99%